Variability of gait initiation in stroke patients: A linear and non-linear approach - Silva, Bruna Brito (2021)
Variability is considered na inherent characteistic of human movement. Linear and nonlinear measures presente diferente expression of variability. Analyze the variability os muscle variation timings, in the ipsilesional (IPSI) and contralesional (CONTRA) limb, during gait initiation (GI), in stroke patients, focusing on linear and non-linear measurements. Cross-sectional observational study, in a sample of seventeen individuals with history of stroke. The variability of linear measurements of muscle variation time was analyzed using the coeficiente of variation (CV). In relation to the variability of nonlinear measurements approximate entropy (ApEn) was used. Regarding the linear analysis, a statistically significant increase was observed in the CV of the tibialis anterior (TA) CONTRA when compared to the TA IPSI, t=2.777, p= 0.013. It should be noted that all the CV means values, of the variation time of the dofferent muscles, are greater than 30%. In the nonlinear analysis, no significant diferences were observed between limbs. The sample of post-stroke individuals under study, exhibit high and dispersed linear variability in muscle variation timings, on the other hand they exhibit a low ApEn, which translates into a variation timing patterns little changeable and with reduced adaptive capacity.